Respuesta :
here x^3-27=0 can be written as
x^3=27 and it also can be,
x^3=3^3
then on comparing both we got ,
x=3..
Hope it will satisfy you
x^3=27 and it also can be,
x^3=3^3
then on comparing both we got ,
x=3..
Hope it will satisfy you
(x-3)(x^2+3x+27) = 0
---
Solve the quadratic factor:
x^2 + 3x + 27 = 0
x = [-3 +- sqrt(9-4*27)/2
---
x = [-3 +- sqrt(-99)]/2
--
x = [-3+-3sqrt(11)i]/2 (2 complex number solutions)
x = 3 (the Real Number solution)
---
Solve the quadratic factor:
x^2 + 3x + 27 = 0
x = [-3 +- sqrt(9-4*27)/2
---
x = [-3 +- sqrt(-99)]/2
--
x = [-3+-3sqrt(11)i]/2 (2 complex number solutions)
x = 3 (the Real Number solution)